Implementasi Kebijakan Peraturan Walikota Serang Nomor 10 Tahun 2021 (Studi Kasus Rehabilitasi Sosial ODGJ Terlantar di Kota Serang) - Santosa, Ariiq Arya; Stiawati, Titi (Innovative: Journal Of Social Science Research, 2025)
Mental health issues, particularly the presence of neglected individuals with mental disorders (ODGJ), have become a critical social concern in Serang City. In response, the Serang City Government issued Mayor Regulation Number 10 of 2021, mandating the Social Service Agency to implement a social rehabilitation program for neglected ODGJ. This study aims to analyze the implementation of this policy using a descriptive qualitative approach and the George C. Edward III policy implementation model, which includes four main dimensions: communication, resources, disposition, and bureaucratic structure. Data collection techniques included in-depth interviews, participatory observation, and documentation involving key stakeholders such as the Social Service Agency, the Municipal Police (Satpol PP), and the Nururrohman Foundation as an operational partner. The findings indicate that the policy has not been implemented optimally. Inter-agency communication remains limited, and public socialization is insufficient. In terms of resources, Serang City lacks government-owned rehabilitation facilities or shelters, and most implementers are honorary staff with no regular incentives. Although the disposition of field workers reflects strong commitment, it is not supported by a structured reward system. The bureaucratic structure is in place, but the absence of detailed technical standard operating procedures (SOPs) has resulted in policy implementation that often relies on improvisation. This study concludes that strengthening human resources, drafting comprehensive SOPs, and establishing dedicated rehabilitation facilities are essential to ensure the sustainability the policy for protecting and rehabilitating neglected ODGJ.